Optimal anaesthetic depth for LMA insertion - Sudeep Krishnappa; Pankaj Kundra (Indian Journal of Anaesthesia, 2011)
Purpose: A fixed dose of propofol administered rapidly can be insufficient or in excess resulting in airway complications and haemodynamic disturbances. This study is designed to assess whether loss of motor response to jaw thrust can be a reliable clinical indicator of anaesthetic depth for laryngeal mask airway (LMA) insertion. Methods: One hundred and twenty ASA I and II patients scheduled for general anaesthesia on day care basis were randomly allocated into two groups. Following pre-oxygenation, anaesthesia was induced to accomplish LMA insertion either with a 3 mg/kg propofol (Group CD, n=60) or in dose to abolish jaw thrust response (Group JT, n=60). Mean arterial pressure (MAP) and heart rate were continuously monitored while LMA insertion conditions were recorded using 6 variable, 3 point score. Results: 85% patients developed apnea in group CD when compared to 2% in group JT, P<0.0001. Despite similar insertion score, propofol consumption was significantly more in group CD when compared to group JT. More than 20% fall of MAP from baseline was noted in group CD after induction but there was no significant hypotension at any time in group JT. Conclusion: Loss of motor response to jaw thrust provides satisfactory LMA insertion conditions.